2019
DOI: 10.1007/s12639-019-01184-6
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological and histopathological diagnosis of a non-native fish (Oreochromis sp.) with a noticeable presence in a natural Brazilian river environment

Abstract: Nile tilapia is an exotic species produced in Brazilian aquaculture. The aim of this study was to constitute a pathological diagnosis in Oreochromis sp. with a noticeable presence in a river in southern Brazil, and to verify the origin of these fish in this natural habitat, an environment with high sanitary precariousness due to discharges of industrial effluents. A total of 30 fish were collected during three sampling events and their health status was assessed by parasitological fauna survey, parasitological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
4
0
4
Order By: Relevance
“…Cichlidogyrus is the parasite genus that occurs naturally in cichlid fish and has the most species among gill parasites, with its 131 different species known [80]. Scutogyrus species can also be dominant in the winter season among fish belonging to the Cichlidae family [81]. de Oliveira Hashimoto, et al [82] reported that Lippia sidoides EO had 100% efficacy against Cichlidogyrus spp.…”
Section: Cichlidogyrus Sppmentioning
confidence: 99%
“…Cichlidogyrus is the parasite genus that occurs naturally in cichlid fish and has the most species among gill parasites, with its 131 different species known [80]. Scutogyrus species can also be dominant in the winter season among fish belonging to the Cichlidae family [81]. de Oliveira Hashimoto, et al [82] reported that Lippia sidoides EO had 100% efficacy against Cichlidogyrus spp.…”
Section: Cichlidogyrus Sppmentioning
confidence: 99%
“…Estudos sobre os parâmetros sanguíneos e histopatológicos são úteis no diagnóstico de doenças em peixes, bem como nas investigações sobre a extensão e compreensão dos danos causados por parasitos nos diversos tecidos dos hospedeiros, em indivíduos e populações de peixes parasitados (Marinho et al, 2015;Rocha et al, 2018;De Oliveira et al, 2019;Lehmann et al, 2020;Rivadeneyra et al, 2020). As avaliações desses parâmetros ajudam a entender os processos fisiológicos nos hospedeiros para manutenção da homeostase orgânica frente a ação de diferentes grupos de parasitos, assim como os efeitos deletérios dos parasitos em seus hospedeiros (Lehmann et al, 2020;Mazur et al, 2020;Sousa et al, 2020). Diversos estudos utilizando ferramentas hematológicas e histopatológicas, bem como sua relação com o parasitismo, têm demonstrado alterações similares provocadas por determinados grupos de parasitos em várias espécies de peixes de diferentes partes do mundo (Biller et al, 2020;Lehmann et al, 2020;Rivadeneyra et al, 2020;Sales et al, 2020).…”
Section: Introductionunclassified
“…As avaliações desses parâmetros ajudam a entender os processos fisiológicos nos hospedeiros para manutenção da homeostase orgânica frente a ação de diferentes grupos de parasitos, assim como os efeitos deletérios dos parasitos em seus hospedeiros (Lehmann et al, 2020;Mazur et al, 2020;Sousa et al, 2020). Diversos estudos utilizando ferramentas hematológicas e histopatológicas, bem como sua relação com o parasitismo, têm demonstrado alterações similares provocadas por determinados grupos de parasitos em várias espécies de peixes de diferentes partes do mundo (Biller et al, 2020;Lehmann et al, 2020;Rivadeneyra et al, 2020;Sales et al, 2020).…”
Section: Introductionunclassified
“…Estudos sobre os parâmetros sanguíneos e histopatológicos são úteis no diagnóstico de doenças em peixes, bem como nas investigações sobre a extensão e compreensão dos danos causados por parasitos nos diversos tecidos dos hospedeiros, em indivíduos e populações de peixes parasitados (Marinho et al, 2015;Rocha et al, 2018;De Oliveira et al, 2019;Lehmann et al, 2020;Rivadeneyra et al, 2020). As avaliações desses parâmetros ajudam a entender os processos fisiológicos nos hospedeiros para manutenção da homeostase orgânica frente a ação de diferentes grupos de parasitos, assim como os efeitos deletérios dos parasitos em seus hospedeiros (Lehmann et al, 2020;Mazur et al, 2020;Sousa et al, 2020).…”
Section: Introductionunclassified